Review of the Literature on the Occurrence of Delirium after Veno-Venous and Veno-Arterial Extracorporeal Membrane Oxygenation: A Systematic Review - Krupa, Sabina (Dement Geriatr Cogn Dis Extra, 2019)
INTRODUCTION: Extracorporeal membrane oxygenation (ECMO) is an extracorporeal gas exchange method which, despite a number of advantages, carries the risk of many complications. ECMO is a modern intensive care method which in many cases is the last resort for the patient. Care and supervision are provided by a multidisciplinary team of specialists: physicians, perfusionists, and nurses. The aim of this review is to analyze the occurrence of delirium in ECMO patients. METHODS: Both authors independently extracted data from all included trials and assessed the risk of bias. A systematic review was performed using the protocol of the Cochrane Collaboration Risk of Bias tool. The search was based on PubMed, Web of Science, and Mendeley. Three articles from recent years have been analyzed in this work. Literature selection was made using the PRISMA checklist. The analyzed literature proves how important the topic of delirium is in ECMO therapy. In the case of pharmacotherapy, there are many combinations of drugs that prevent the occurrence of the delirium phenomenon. RESULTS: This work deals with the subject of delirium after ECMO, which is not a common subject in the popular literature. Many of the elements mentioned in the articles analyzed show how important this topic is. The authors place great emphasis on the elements which are not related to pharmacotherapy and the prevention of delirium. For the prevention of delirium after ECMO, a psychological approach to the patient is important. As far as pharmacotherapy is concerned, it is the last element to be taken into account in the prevention of delirium in ECMO patients. An overview of the literature indicates that the subject of nursing care has been omitted; however, there are tools which allow nurses to assess delirium in patients. CONCLUSION: Delirium in patients undergoing ECMO therapy is a topic that has not been fully described in the literature. This review of the literature shows how important it is to treat a patient with delirium during this therapy and how important it may be to have an early diagnosis of delirium to prevent complications.